A Potential Link Between Prolonged Cork Exposure and Intestinal-Type Sinonasal Adenocarcinoma – Special Findings of a Retrospective Cohort Analysis - Alpuim Costa, Diogo; Monteiro, Ana; André, Teresa; Esteves, Susana; Sargento, Isabel; Ferreira, Margarida; Alexandre, Teresa; Clara, Ana; Freire, João; Moreira, António (Frontiers in Oncology, 2020)
Introduction intestinal-type sinonasal adenocarcinoma (ITAC) is a rare epithelium tumor of the nasal cavities and paranasal sinuses. Exposure to wood and leather dusts is a strong etiological factor related to its development. Prolonged cork exposure has rarely been associated. Materials and Methods thirty-seven-year (1981–2018) retrospective cohort analysis of all consecutive patients with sinonasal cancer (SNC) followed at our institution. Medical records were reviewed to determine patient demographics, occupational/environmental exposure, location and extent of the tumor, stage, histopathology findings, treatment strategies, and oncologic outcomes. Survival analysis was done using Kaplan–Meier method. Results we evaluated 379 patients with SNC, including 39 (10.3%) ITAC. Patient median age was 73 years (range 49–87), 56% male and 69% with identified professional occupational exposure (54% for cork; 69.2% considering only those for which an agent has been identified). Seventy-two percent had locally advanced disease (stage III or IVA–B). The initial treatment was surgery in 77%, and 54% received adjuvant radiotherapy. The median time to progression, progression-free survival, and overall-survival was 2.36 years (95% CI 1.54–8.70), 1.96 years (95% CI 1.43–3.74), and 3.51 years (95% CI 2.33–10.02), respectively. Conclusion ITAC is an uncommon malignancy that grows silently, which contributes to delayed diagnosis, advanced stage and low survival rates. In our cohort, we observed a high prevalence of cork occupational exposure. This finding may lead to the implementation of protection measures and suggest a potential link to be further studied.